Performance Analysis of Sea Water Cooling Pumps on The Smoothness of The Main Engine Cooling System on The Mt. Fail - Arda Billy, Mohammad; Kurniawan, Didik Sulistyo; Sursina, Sursina; Mudakir, Mudakir (International Journal of Advanced Multidisciplinary, 2023)
The main engine sea water cooling pump is a type of centrifugal pump as one of the pumps that is often found in the ship machinery industry working on the principle of impeller rotation as a fluid transfer element driven by a propulsion engine. The liquid inside will rotate due to the impetus of the blades and cause a centrifugal force which causes the liquid to flow from the middle of the impeller and out through between the blades and leave the impeller at high speed. The sea water cooling pump has a very important role in supporting the cooling system process on the main engine. If the coolant pump does not work properly, it will result in a less than optimal cooling system. Like the problems the author experienced when carrying out sea practice on the MT ship. This causes problems with the lack of maximum performance from the pump impeller and pump vibrations that are too high. which resulted in affecting the performance of the main engine and disrupting the operation of the ship. The purpose of this research is to find out the cause of the less than optimal performance of the impeller on the pump and find a solution. and to find out the cause of too high vibration in the pump and find a solution. While this research method is a qualitative descriptive research method. The results of this study are expected to be useful in science as a contribution to ideas related to the analysis of the performance of seawater cooling pumps to support ship operations.